Faktor Penetapan Harga Jual dan Distribusi Pendapatan dalam Perspektif Islam - Indah Dwi Rizki Amas (Dharma Ekonomi, 2025)
The role of economics in human life has become increasingly significant in the modern era as it serves as a foundation for meeting daily needs and achieving collective welfare. This study aims to analyze how Islamic economic principles regulate price determination in markets and income distribution to ensure fairness and social balance. The research adopts a qualitative approach through library research by reviewing classical Islamic literature, modern economic works, and Qur’anic interpretations related to economic justice. The findings show that Islam emphasizes justice, equality, and welfare as the foundation of all economic activity. Price setting in Islam must reflect fairness, avoiding exploitation and ensuring that transactions bring mutual benefit to both sellers and buyers. Meanwhile, income distribution is directed toward social equity through the implementation of zakat, infaq, and shadaqah, which serve as instruments for wealth redistribution and poverty alleviation. The implication of this study is that the application of Islamic economic principles can provide a moral and sustainable alternative to conventional capitalist systems by promoting fairness, social responsibility, and economic stability within society.